2014
DOI: 10.1038/nrm3869
|View full text |Cite|
|
Sign up to set email alerts
|

Capping protein regulators fine-tune actin assembly dynamics

Abstract: Capping protein (CP) regulates actin polymerization by binding the barbed end of an actin filament, which blocks addition and loss of actin subunits. Recent structural and biochemical studies provide new insight into how cells control the actin capping activity of CP. Several molecules indirectly regulate CP by interacting with filament barbed ends and preventing binding of CP; others bind directly to CP and sterically block its interaction with an actin filament. A diverse and otherwise unrelated set of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
286
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 259 publications
(291 citation statements)
references
References 178 publications
(198 reference statements)
3
286
0
2
Order By: Relevance
“…One prediction of this model is that cells expressing a version of CP that cannot see the CPI motif in CARMIL and related proteins (e.g., CD2AP and CKIP) should phenocopy Arp2/3-inhibited cells. This prediction has recently received direct support by the work of Edwards et al (29).Studies using gene ablation or RNAi have demonstrated that CARMIL proteins play important roles in the formation of cortical actin structures like pseudopodia and macropinocytic crowns in Dictyostelium and lamellipodia in tissue culture cells (1,19). In contrast, relatively little is known regarding the importance of V-1 in vivo (30-32), especially with respect to effects on actin assembly and organization.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…One prediction of this model is that cells expressing a version of CP that cannot see the CPI motif in CARMIL and related proteins (e.g., CD2AP and CKIP) should phenocopy Arp2/3-inhibited cells. This prediction has recently received direct support by the work of Edwards et al (29).Studies using gene ablation or RNAi have demonstrated that CARMIL proteins play important roles in the formation of cortical actin structures like pseudopodia and macropinocytic crowns in Dictyostelium and lamellipodia in tissue culture cells (1,19). In contrast, relatively little is known regarding the importance of V-1 in vivo (30-32), especially with respect to effects on actin assembly and organization.…”
mentioning
confidence: 95%
“…Studies using gene ablation or RNAi have demonstrated that CARMIL proteins play important roles in the formation of cortical actin structures like pseudopodia and macropinocytic crowns in Dictyostelium and lamellipodia in tissue culture cells (1,19). In contrast, relatively little is known regarding the importance of V-1 in vivo (30-32), especially with respect to effects on actin assembly and organization.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To circumvent this promiscuity, we focused our investigation on the early intracellular trafficking events of newly synthesized GPRC5B proteins. We show that most newly synthesized GPRC5B protein is released in exosomes as opposed to microvesicles and that an adaptor protein, CD2AP (27), mediates internalization of cell surfacelocalized GPRC5B as an early event. Surprisingly, we found that the internalized GPRC5B proteins subsequently accumulated in the Golgi complex prior to exosomal release and that the L-type lectin LMAN2 (28,29) impedes the exosomal release of GPRC5B specifically from the trans Golgi network (TGN), possibly by interfering with the physical association of GPRC5B and GGA1, an adaptor protein implicated in TGN-to-endosome trafficking (30,31), or possibly by opposing the biosynthetic secretory trafficking through TGN-to-endoplasmic reticulum (ER) retrograde transport (28).…”
mentioning
confidence: 99%